Personality traits and physical activity in patients with gambling disorder attending a rehabilitation center. An observational study - Fierro, Inmaculada; Fernández-Prieto, Raúl; Fernández-Parra, Alicia; Herrero-Martín, Miriam; Herrero, Azael J. (Frontiers in Psychology, 2024)
Objective Problem gambling is associated with various negative health behaviors, such as physical inactivity. However, physical activity may also be used as a coping mechanism to manage stress and anxiety. This study aimed to investigate whether personality traits are associated with physical activity levels in individuals attending a rehabilitation center for gambling disorder (GD). Methods An observational study was conducted in 71 patients belonging to a Gamblers’ Recovery Association. All of them completed a socio-demographic questionnaire, the Exploratory Personality Questionnaire-III (CEPER-III) and the International Physical Activity Questionnaire (IPAQ). Comparisons with general population and association between personality traits and physical activity were analyzed. Results The study sample predominantly consisted of male participants (91.5%), with the majority having an educational attainment of compulsory schooling or less (70.4%). Additionally, a substantial proportion of participants exhibited school-related problems (43.7%) and had a history of mental health issues (33.8%). Compared to the general population, individuals in the CEPER-III cohort demonstrated significantly lower scores in the following personality traits: paranoid (p < 0.05), histrionic (p < 0.001), narcissistic (p < 0.001), passive-aggressive (p < 0.05), and sadistic (p < 0.01). Multivariate logistic regression analysis indicated that the antisocial, borderline, obsessive-compulsive, and self-destructive personality traits were significantly associated (p < 0.05) with the level of physical activity. Conclusion This study found a link between personality traits and physical activity levels in patients with GD. Gamblers with higher scores on obsessive-compulsive and self-destructive personality traits were more likely to fall into the moderate-high physical activity group. In contrast, those with higher scores on antisocial and borderline personality traits were more likely to be classified in the low physical activity group.